2020
DOI: 10.1051/0004-6361/202037439
|View full text |Cite
|
Sign up to set email alerts
|

Pal 13: its moderately extended low-density halo and its accretion history

Abstract: We present results on the basis of Dark Energy Camera Legacy Survey (DECaLS) DR8 astrometric and photometric data sets of the Milky Way globular cluster Pal 13. Because of its relative small size and mass, there has not been yet a general consensus about the existence of extra-tidal structures around it. While some previous results claim for the absence of such features, others have shown that the cluster is under the effects of tidal stripping. From DECaLS g, r magnitudes of stars placed along the cluster Mai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
3
9
0
Order By: Relevance
“…The existence of MPs in Pal 13 supports the statement that this phenomenon is not unique in Galactic GCs formed in − situ (e.g., Li & de Grijs 2019;Milone et al 2020). Besides its proposed accreted origin, Pal 13 is suggested to be experiencing tidal stripping (Yepez et al 2019;Piatti & Fernández-Trincado 2020). Hamren et al (2013) found that Pal 13 has lost a considerable amount of mass, which is related to its low present-day cluster mass.…”
Section: And N Abundancessupporting
confidence: 59%
See 3 more Smart Citations
“…The existence of MPs in Pal 13 supports the statement that this phenomenon is not unique in Galactic GCs formed in − situ (e.g., Li & de Grijs 2019;Milone et al 2020). Besides its proposed accreted origin, Pal 13 is suggested to be experiencing tidal stripping (Yepez et al 2019;Piatti & Fernández-Trincado 2020). Hamren et al (2013) found that Pal 13 has lost a considerable amount of mass, which is related to its low present-day cluster mass.…”
Section: And N Abundancessupporting
confidence: 59%
“…This indicates MPs exist in the GC Pal 13. This GC recently attracts attention because of its revealed peculiarity under deep photometric observations, e.g., high binary fraction (Clark et al 2004), experiencing tidal dissolution (Piatti & Fernández-Trincado 2020), and the discovery of tidal tails (Shipp et al 2020). Our novel discovery of MPs in Palomar 13 is consistent with the suggested large mass loss, assuming that MPs are preferentially formed in large initial mass GCs (Conroy & Spergel 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of two-body relaxation, less massive stars are candidates to escape the cluster more easily than more massive ones (Balbinot & Gieles 2018). Hence, fainter cluster main sequence (MS) stars are usually used to search for extra-tidal structures around globular clusters (see Piatti & Fernández-Trincado 2020, and references therein). We, therefore, take advantage of the well-delineated MS shown in Fig.…”
Section: Stellar Density Mapsmentioning
confidence: 99%